Violent women: treatment approaches and psychodynamic considerations. Issue 2 (18th June 2018) - McKeown, Annette; Harvey, Ellen
Abstract : Purpose: Some psychodynamic approaches conceptualise female violence as a communication of experiences too difficult to think about. As practitioners, understanding what may be too painful to be thought about is incredibly important in assessment and treatment of forensic populations. Incorporating psychodynamic concepts such as splitting, transference, projection and counter-transference into formulation can be extremely helpful in understanding and formulating women's risk of violence. The purpose of this paper is to introduce how psychodynamic concepts can be incorporated into understanding, assessment, formulation and treatment with this complex client group. This paper will also outline treatment approaches with this population. Design/methodology/approach: This paper will review existing psychodynamic literature and apply this knowledge to working with violent female offenders. Translating theory into reflective practice will be presented. Findings: This paper presents the value of incorporating psychodynamic considerations into existing strategies of understanding and working with violent female offenders. Ways forwards and research directions are proposed. Research limitations/implications: This paper is focussed primarily on psychodynamic approaches to understanding this population Practical implications: Psychodynamic concepts can add an additional dimension to formulation, supervision and treatment approaches with this population. Examining the meaning of violence perpetrated by women as well as enactments can improve practitioner's depth of understanding. Empirical research examining the benefits of psychoanalytic supervision would be extremely useful to explore the impact on formulation, treatment approaches, treatment effectiveness, staff well-being and staff retention. Originality/value: There is a lack of literature considering the application of psychodynamic constructs to help formulation of complex female offenders in the Offender Personality Disorder Pathway for women.